Long Noncoding RNA TUG1 Promotes the Function in ox-LDL-Treated HA-VSMCs via miR-141-3p/ROR2 Axis - Yu Tang; Jing Hu; Zhiying Zhong; Yanfeng Liu; Yunxia Wang (Cardiovascular Therapeutics)
Background. Atherosclerosis (AS) is a common severe disease around the world. The merging paper reported that long noncoding RNAs (lncRNAs) took part in diversified pathological processes of AS, although the mechanism remains unknown. This study is aimed at uncovering the profile of lncRNA taurine-upregulated gene 1 (TUG1), which has biological function, and potential mechanism in AS progression in vitro. Methods. Oxidized low-density lipoprotein (ox-LDL) was used for AS model construction in vitro. Levels of lncRNA TUG1, miR-141-3p, and receptor tyrosine kinase-like orphan receptor 2 (ROR2) were detected by quantitative real-time polymerase chain reaction (qRT-PCR) in AS tissues or in ox-LDL-treated vascular smooth muscle cells (HA-VSMCs). The biofunctional effects were examined by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) and transwell assays. The expression of proliferation-related proteins (CyclinD1, Ki-67) and metastasis-associated proteins (β-catenin, Vimentin) and ROR2 in cells was determined by western blot analysis. The potential binding sites were predicted by starBase software online and confirmed by dual-luciferase reporter analysis. Results. The expression of TUG1 and ROR2 was promoted in AS tissues and ox-LDL-treated HA-VSMCs. While the low expression of miR-141-3p negatively correlated with that of TUG1 or ROR2 in AS tissues. Silencing of TUG1 inhibited the proliferation, migration, invasion, and metastasis in ox-LDL-treated HA-VSMCs. Moreover, the putative binding sites between miR-141-3p and TUG1 or ROR2 were predicted by starBase software online. Also, miR-141-3p deletion reversed the positive effects of TUG1 knockdown on cells. Besides, downregulation of miR-141-3p disrupted the biofunctional results from ROR2 silencing. Conclusion. TUG1 enhanced the progression of AS in vitro by regulating the miR-141-3p/ROR2 axis.